(3cJGH GdQhMs - (3Wg GdOejGWj , Wg Hf eMeO bWQjg GdOejGWj,J (B1325 (3g` s ((3YHOGddg Hf CMeO GdfHQGhi s)
(3ChdgG (B:s
(3GdeSCdI GdChdi hgh gd jYQa GdCehGJ HRjGQI GdCMjGA hSdGege Ydjge s
(3BNQgG (B:s
(3TQhQCfaSfG hSjFGJ CYeGdfG hGf dG JLYdfG ef GdCNSQjf CYeGd GdPjf Vd SYjge ai GdMjGI GdOfjG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B44s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1421s
Keywords: (3GdadSaI hGdefWbs